Perbedaan Kejadian Karies Gigi Molar Satu Permanen dan Indeks DMF-T pada Siswa SD di Wilayah Perkotaan dan Pedesaan (Studi Cross Sectional) - Syukra Alhamda; Nabila Putri; Eriyati Eriyati (Poltekkes Kemenkes Padang, 2026)
Differences in environmental conditions, access to health services, and oral health maintenance behavior are thought to influence dental caries among school-age children, particularly in the first permanent molars. This study aimed to analyze the differences in first permanent molar caries and DMF-T index among sixth-grade elementary school students in urban and rural areas.This study was an analytic study with a cross sectional approach conducted at SDN 06 Aur Tajungkang Tengah Sawah, Bukittinggi City, and SDN 22 Koto Tangah, Agam Regency. The sample consisted of 50 students selected using the total sampling technique. Data were collected through examinations of first permanent molar caries depth and DMF-T index. Data analysis was performed using the Mann Whitney U Test. The results showed that superficial caries were more common among students in urban areas, while profunda caries were more common among students in rural areas. The mean DMF-T index in urban students was higher (3.97) than in rural students (1.86). Statistical analysis showed significant differences in superficial caries (p=0.001), profunda caries (p=0.023), and total DMF-T index (p=0.040), while media caries, missing component, and filling component showed no significant differences. In conclusion, there were differences in the pattern of first permanent molar caries and DMF-T index between elementary school students in urban and rural areas. Promotive and preventive oral health efforts tailored to regional characteristics are needed through oral health education and regular dental examinations at schools.